2001
DOI: 10.1007/pl00008569
|View full text |Cite
|
Sign up to set email alerts
|

The detection and occurrence of circulating antigens of Trichinella spiralis during worm development

Abstract: Four enzyme-based immunoassays were compared in detecting circulating antigens (CA) of Trichinella spiralis, i.e. microfluorescence, dissociated enhanced lanthanide fluoroimmunoassay (DELFIA), enhanced chemiluminescence and enzyme-linked immunosorbent assay (ELISA). Parameters which could affect the sensitivity and specificity of the assays were evaluated. Different combinations of polyclonal antibody (PA) and five monoclonal antibodies (mAbs) against the excretory/secretory antigens of the nematode were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A significant elevation of IgG 1 is often observed in trichinellosis (Li & Ko, 2001;Kołodziej-Sobocińska et al, 2006). The protective isotypes IgG 1 and IgG 2 are involved in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…A significant elevation of IgG 1 is often observed in trichinellosis (Li & Ko, 2001;Kołodziej-Sobocińska et al, 2006). The protective isotypes IgG 1 and IgG 2 are involved in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently the host response to muscle invasion has been studied in animals genetically different for immune status, focusing on the cytokine pattern and the type of cell subsets infiltrating the muscle fibers in both T. spiralis and T . pseudospiralis [79]. The results have shown that cell infiltration is higher in BALB/c than in CBA/N mice and even lower in nude mice in response to T. spiralis, whereas during infection with T. pseudospiralis, a lower presence of cells, compared to T. spiralis infection, is observed in BALB/c mice.…”
Section: Immune Response At the Muscle Levelmentioning
confidence: 61%
“…However, immunodiagnostic methods developed using these MAbs had problems relating to sensitivity, specificity, and reproducibility. The ES antigens of T. spiralis muscle larvae have been shown to the useful antigens for producing MAbs for use in the development of immunodiagnostic techniques for trichinellosis (Zhu et al, 1990;Srimanote et al, 2000;Li & Ko 2001;Zumaquero-Ríos et al, 2012). The aim of the present study was to generate and characterize MAbs against ES antigens of T. spiralis muscle larvae, which would provide a foundation for the development of specific immunodiagnostic techniques for the specific early diagnosis of trichinellosis.…”
Section: Introductionmentioning
confidence: 99%